PELATIHAN MENGUKUR VALIDITAS SOAL ESAI DAN CAMPURAN UNTUK MENINGKATKAN KOMPETENSI GURU SEKOLAH DASAR - Agus Agung Permana; Pinta Deniyanti Sampoerno; Ellis Salsabila; Qorry Meidianingsih; Wardani Rahayu; Ajeng Wijayanti; Cyintias Hanum Fuad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This community service activity is motivated by the demand to improve teachers' pedagogical competence in planning, implementing, and evaluating learning outcomes comprehensively. The main problem in the field shows that elementary school (SD) teachers in Gegerbitung District, Sukabumi Regency, still need to improve their analytical skills to validate the test instruments they construct independently, especially for essay and mixed-type questions. The purpose of this activity is to provide theoretical and practical training on item validity calculation techniques to ensure evaluation instruments accurately measure learning achievement. The activity used an educative-participatory method that included material presentation, interactive discussion, and simulation assisted by data processing software. The face-to-face activity held at SMP Negeri 1 Gegerbitung was attended by 12 participants. Program evaluation was conducted through cognitive assessments (pre-test and post-test) and participant response questionnaires. The analysis results showed a 22% increase in the participants' average score, rising from 63 (63%) in the pre-test to 85 (85%) in the post-test, with 100% of participants agreeing that the training materials were highly systematic and applicable. The conclusion of this service is that the training proved effective in enhancing teachers' cognitive and technical abilities to validate assessment instruments, thereby supporting the development of reliable item banks at the institutional level. ABSTRAK Kegiatan pengabdian ini dilatarbelakangi oleh kebutuhan peningkatan kompetensi pedagogik guru dalam merencanakan, melaksanakan, dan mengevaluasi hasil pembelajaran secara komprehensif. Permasalahan utama di lapangan menunjukkan bahwa guru-guru Sekolah Dasar (SD) di Kecamatan Gegerbitung, Kabupaten Sukabumi, masih membutuhkan peningkatan keterampilan analitis untuk memvalidasi instrumen tes yang mereka susun secara mandiri, terutama pada bentuk soal esai dan campuran. Kegiatan ini bertujuan untuk meningkatkan kompetensi guru dalam melakukan analisis validitas butir soal melalui pelatihan dan pendampingan. Pelaksanaan kegiatan menggunakan metode edukatif-partisipatif yang meliputi pemaparan materi, diskusi interaktif, serta simulasi perhitungan statistik dan peranti lunak pengolah angka. Kegiatan yang diselenggarakan secara luring di SMP Negeri 1 Gegerbitung ini diikuti oleh 12 peserta. Evaluasi program dilakukan melalui pengukuran kognitif (pre-test dan post-test) serta angket respons peserta. Hasil analisis menunjukkan adanya peningkatan skor rata-rata peserta sebesar 22%, yakni dari 63 (63%) pada pre-test menjadi 85 (85%) pada post-test, serta seluruh peserta (100%) menyatakan setuju bahwa materi pelatihan sangat sistematis dan aplikatif. Simpulan dari kegiatan ini adalah pelatihan terbukti efektif meningkatkan kemampuan kognitif dan teknis guru dalam memvalidasi instrumen penilaian, sehingga berpotensi mendukung pengembangan bank soal yang andal di tingkat satuan pendidikan.